Identification of Robust Biomarkers for Early Predicting Efficacy of Subcutaneous Immunotherapy in Children With House Dust Mite-Induced Allergic Rhinitis by Multiple Cytokine Profiling - Xie, Shaobing; Fan, Ruohao; Tang, Qingping; Cai, Xiao; Zhang, Hua; Wang, Fengjun; Xie, Shumin; Gao, Kelei; Zhang, Junyi; Xie, Zhihai; Jiang, Weihong (Frontiers in Immunology, 2022)
Background: Subcutaneous immunotherapy (SCIT) is an effective treatment for children with allergic rhinitis (AR), but its efficacy fluctuates among patients. There are no reliable candidate biomarkers for monitoring and predicting the response to SCIT. The present study aims to identify novel biomarkers for early predicting the efficacy of SCIT in pediatric AR patients based on multiple cytokine profiling. Methods: We prospectively recruited 72 children with house dust mite (HDM)-induced AR who were assigned to receive SCIT. The serum samples were collected and multiple cytokine profiling was conducted by Luminex assay at baseline. All patients were followed-up for 1 year and then categorized into effective and ineffective group based on their efficacy, and levels of 48 selected cytokines were tested and compared between the two groups. The potential cytokines were further validated by enzyme-linked immunosorbent assay (ELISA) in a cohort with 54 responders and 26 non-responders. Results: Sixty-nine of 72 children completed one-year follow-up schedule with 46 included in effective group and 23 in ineffective group. The results of multiple cytokine profiling showed that 15 cytokines (eotaxin, G-CSF, GM-CSF, IFN-γ, IL-12(p40), IL-13, IL-15, IL-16, IL-4, MIF, MIP-1α, RANTES, SCF, SDF-1α and VEGF) were dysregulated between effective and ineffective group (all P < 0.05). Unadjusted and adjusted multivariate analysis models highlighted that serum eotaxin, IFN-γ, IL-4 and MIF levels closely associated with the efficacy of SCIT in pediatric HDM-induced AR patients. In addition, receiver operating characteristic (ROC) curves revealed potential values of these four biomarkers in predicting the response to SCIT. Further ELISA validation results in the cohort of 80 pediatric patients demonstrated that serum eotaxin and IL-4 levels were elevated in responders while IFN-γ levels decreased in responders (all P < 0.05). ROC curves demonstrated that serum IL-4 exhibited more reliable accuracy in predicting SCIT efficacy than eotaxin and IFN-γ. Conclusion: Our discover–validation study suggested that cytokines including IL-4, eotaxin and IFN- γ may serve as robust biomarkers for early predicting response of SCIT in children with HDM-induced AR. These results strengthen the evidence that cytokines were associated with the response of SCIT and contributed to understand its underlying therapeutic mechanisms.